INTEGRATED OPTIMIZATION MODEL OF MANUFACTURING AND TRANSPORTATION PROCESSES - R. S. Rogulin; D. E. Pleshanov; P. V. Nechaev (Дискурс)
This paper is devoted to constructing a linear mixed-integer model, finding a method and selecting an algorithm to determine the optimal solution to the production and transportation problem. This task can be attributed to non-trivial combinatorial problems on decision-making at an enterprise. This article contains a model of generalization of three previously known linear programming problems: production problems, time accounting tasks, and service flow problems. The target setting that integrates all three of the above problems into one, applies to the case when a manufacturing facility declares itself bankrupt and tries to manufacture products from the remains of raw materials for further sale and delivery of the goods produced meeting road system features, maximizing the profit and minimizing carrying costs. It is shown that such a problem can solve and visualize the package Matlab. Possible economic situations are presented where this model could be relevant. A number of possible upgrades to the model of this problem are considered.